Do wealthy politicians underreport their income? Evidence from general election data - Ray, Soumyajit; Singh, Ram (University of Delhi, 2022)
The income reporting behaviour of wealthy Indians is a critical public finance issue. It has remained under-researched due to the lack of data sources required for the purpose. In this article, we use a new and unique source of information to examine the income reporting behaviour of politicians from across a wide range of wealth spectrums. The new dataset compiled and used by us is based on the affidavits filed by contestants in the 2014 and 2019 Lok Sabha elections. We find that, on average, wealthier candidates and their households report less income relative to their wealth. Consequently, most affluent families do not necessarily figure among those reporting the highest income to tax authorities. The income declared to tax authorities by the 10% least wealthy candidates is more than 300% of their wealth. In contrast, the income level reported by the wealthy group is a tiny fraction of their wealth. The wealthiest 5% of candidates have reported income amounting to only 3.4% of their wealth. The reported income of the wealthiest 0.1% is less than 2% of their wealth. The results are very similar for the households. We show that the abysmally low income reported by the wealthy groups stands in sharp contrast to the returns on assets owned by them. We argue that the missing income of the wealth groups is a result of the creative accounting and financial engineering used by them to avoid paying taxes.